Parametric Analysis of a Modular Solar Drying and Packed Bed Thermal Energy Storage System - Pailahueque-Barahona, N (Elsevier Ltd, 2025)
Solar drying is an effective technology for reducing fossil fuel consumption in food preservation. However, its reliability is limited by the availability of solar radiation. Integrating thermal energy storage (TES) can enhance system efficiency by extending operation beyond peak sunlight hours. The use of industrial by-products with high thermal capacities, such as metallurgical slags, offers a promising alternative for TES. However, the integration of solar collectors and TES remains a challenge, as system performance depends on the configuration and operational strategy. This study presents a parametric analysis of a solar drying system for kiwifruit slices, incorporating solar air collectors and a packed-bed TES unit. A validated mathematical model, supported by experimental data, is used to assess three different schemes for discharging TES, considering flow-switching strategies, six solar field configurations, and the role of an auxiliary heater in maintaining drying reliability throughout the year. The findings indicate that early switching the airflow, combined with smaller TES volumes and one solar collector, achieves a 40.53% cost reduction compared to a conventional drying configuration. The results highlight that balancing the system s components significantly enhances solar drying performance. © 2025 International Solar Energy Society